The Role of Posters as Media for Anti-Bullying Counseling among Teenagers: A Literature Review: Peran Poster sebagai Media Penyuluhan Anti-Bullying di Kalangan Remaja: Kajian Literatur - faida hapsari; Muhamad Rifa'i Subhi (Program Studi Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas Sumatera Selatan, 2025)
ABSTRACT Bullying is one of the serious problems that still often occurs among adolescents and has a negative impact on the mental health of victims. Counseling is an effective method in increasing awareness about the dangers of bullying, and the selection of appropriate counseling media is very important so that the message can be conveyed optimally. This study aims to analyze the effectiveness of using posters as media for anti-bullying education based on a literature study. This research uses a literature review method with a descriptive qualitative approach. The results of the review show that posters are effective visual media in attracting adolescents' attention, simplifying information, and increasing understanding and awareness about bullying. Attractive visual design, the use of appropriate language, and the relevance of the content to the lives of adolescents are determining factors the success of message delivery. Thus, posters are feasible to use as part of anti-bullying counseling strategies in school and youth environments. Keywords: poster, counseling, bullying, youth, visual media ABSTRAK Bullying merupakan salah satu permasalahan serius yang masih sering terjadi di kalangan remaja dan berdampak negatif terhadap kesehatan mental korban. Penyuluhan menjadi metode efektif dalam meningkatkan kesadaran mengenai bahaya bullying, dan pemilihan media penyuluhan yang tepat sangat penting agar pesan dapat tersampaikan secara optimal. Kajian ini bertujuan untuk menganalisis efektivitas penggunaan poster sebagai media penyuluhan anti-bullying berdasarkan studi literatur. Penelitian ini menggunakan metode kajian literatur dengan pendekatan kualitatif deskriptif. Hasil telaah menunjukkan bahwa poster merupakan media visual yang efektif dalam menarik perhatian remaja, menyederhanakan informasi, dan meningkatkan pemahaman serta kesadaran tentang bullying. Desain visual yang menarik, penggunaan bahasa yang sesuai, dan relevansi isi dengan kehidupan remaja menjadi faktor penentu keberhasilan penyampaian pesan. Dengan demikian, poster layak digunakan sebagai bagian dari strategi penyuluhan anti-bullying di lingkungan sekolah dan remaja. Kata kunci: poster, penyuluhan, bullying, remaja, media visual